Approximate Controllability of Fractional Integrodifferential Evolution Equations. (20th May 2013) - Ganesh, R.; Sakthivel, R.; Mahmudov, N. I.; Anthoni, S. M.
Abstract : This paper addresses the issue of approximate controllability for a class of control system which is represented by nonlinear fractional integrodifferential equations with nonlocal conditions. By using semigroup theory, p -mean continuity and fractional calculations, a set of sufficient conditions, are formulated and proved for the nonlinear fractional control systems. More precisely, the results are established under the assumption that the corresponding linear system is approximately controllable and functions satisfy non-Lipschitz conditions. The results generalize and improve some known results.